Integrating family planning into HIV care in western Kenya: HIV care providers' perspectives and experiences one year following integration - Newmann, Sara J. (AIDS Care, 2015)
With high rates of unintended pregnancy in sub-Saharan Africa, integration of family planning (FP) into HIV care is being explored as a strategy to reduce unmet need for contraception. Perspectives and experiences of healthcare providers are critical in order to create sustainable models of integrated care. This qualitative study offers insight into how HIV care providers view and experience the benefits and challenges of providing integrated FP/HIV services in Nyanza Province, Kenya. Sixteen individual interviews were conducted among healthcare workers at six public sector HIV care facilities one year after the implementation of integrated FP and HIV services. Data were transcribed and analyzed qualitatively using grounded theory methods and Atlas.ti. Providers reported a number of benefits of integrated services that they believed increased the uptake and continuation of contraceptive methods. They felt that integrated services enabled them to reach a larger number of female and male patients and in a more efficient way for patients compared to non-integrated services. Availability of FP services in the same place as HIV care also eliminated the need for most referrals, which many providers saw as a barrier for patients seeking FP. Providers reported many challenges to providing integrated services, including the lack of space, time, and sufficient staff, inadequate training, and commodity shortages. Despite these challenges, the vast majority of providers was supportive of FP/HIV integration and found integrated services to be beneficial to HIV-infected patients. Providers' concerns relating to staffing, infrastructure, and training need to be addressed in order to create sustainable, cost-effective FP/HIV integrated service models.